A Qualitative Study of Interactional Pathology among the spouses of Men with Morbid Jealousy from the Viewpoint of Clinical Family Specialists - مرضیه سلطانی; مریم فاتحی‌زاده; سید احمد احمدی; محمد رضا عابدی; مهرداد صالحی; رضوان السادات جزایری (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2017)
Aim and Background: An individual pathology observed in families is morbid jealousy. Thus, the aim of the present study was to examine the views of family therapy specialists about interactional damages in spouses of men with morbid jealousy. Methods and Materials: The present research was a qualitative (phenomenological) study. The search population consisted of all specialists in the field of psychological family therapy. The participants consisted of 8 specialists with experiences in psychological family therapy. Data were collected through semi-structural interviews. The gathered data were analyzed through systematic method in the three steps of description, reduction, and interpretation. Findings: The results showed that from among 489 sentences related to interactional damages, 122 concepts were extracted in open coding that were disaggregated into 23 subthemes in axial coding. Finally, data were summarized into 9 categories of pathologies related to solving conflicts, communication styles, sexual relationship, communication with children, and communication with the spouse regarding familial and household issues, and cognitive, behavioral, and emotional damages which were problematic to the relationship. Conclusions: It can be concluded that, from the viewpoint of family specialists, men with morbid jealousy cause damages in their families that increase the probability of family disintegration.